ANALYSIS OF STUDENT PERCEPTIONS ON THE USE OF ONLINE LEARNING APPLICATIONS USING THE RASCH MODEL IN PHYSICS LEARNING - Dewa Gede Eka Setiawan; Vivit Idrus; Muhammad Yusuf; Trisnawaty Junus Buhungo; Ritin Uloli (Universitas Negeri Gorontalo, 2022)
SMAN 1 Tapa initially used the Zoom and Google Meet applications, but there were still many students who were late for learning due to their difficult circumstances in getting internet coverage, so the teachers decided to change the application by using Classroom and Whatsapp to minimize student delays in learning. This study aims to describe students' perceptions of the use of online learning applications using Rasch modeling in physics learning. This research method is descriptive qualitative. The results of this study indicate that students' perceptions based on absorption indicators of object stimuli from outside the individual, students prefer online learning using Classroom and Whatsapp applications. Based on the indicators of understanding or understanding of the object, students understand and understand physics learning. Based on the indicators of individual evaluation of the object, students are enthusiastic and motivated in learning physics. Thus, it can be concluded that students' perceptions of online learning using the classroom and whatsapp applications can help and facilitate students in the learning process during the pandemic in class XI IPA 1.